Liberia : First Review Under the Extended Credit Facility Arrangement and Request for Waiver of Nonobservance of a Performance Criterion and Modification of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2013)
This paper describes Liberia's First Review Under the Extended Credit Facility Arrangement and Request for Waiver of Nonobservance of a Performance Criterion and Modification of Performance Criteria. Nonresource real GDP growth, in particular, while still on an upward trend has been revised down for 2013, reflecting the sluggish pace of public investment. Nonresource growth is expected to pick up in the medium term, in line with an expected increase in public investment albeit the investment path is somewhat more moderate than originally planned and provided project execution speeds up.